The immune mystery : a doctor's impassioned quest to solve the puzzle of autoimmune disease - Kåss, Anita, 1979-; Jelstad, Jørgen, 1979- (Greystone Books, 2021)
"Our bodies are protected by a complex defense system - an army that stands ready to combat dangerous invaders. But sometimes wires get crossed and our defenders turn against the body they are supposed to protect. Then we fall prey to autoimmune diseases such as rheumatoid arthritis, lupus, or type 1 diabetes. In all there are more than a hundred such diseases, which can ruin lives and sometimes end them prematurely. And these diseases are on the rise. The Immune Mystery, by rheumatologist and researcher Anita Kåss, is the story of Kåss's quest to solve the puzzle of autoimmune disease and find a potential cure. It is a highly personal quest: Kåss's mother contracted rheumatoid arthritis after giving birth to her, and died when her daughter was only thirteen. The book follows Kåss's journey as a researcher--from the day of her mother's funeral in 1993, when she first started reading about rheumatoid arthritis, to the moment in 2017 when she is interviewed on Scandinavia's biggest talk show about a potentially revolutionary discovery that has earned her a record-breaking deal with a Japanese pharmaceutical company. Inspirational and compelling,The Immune Mystery is both a window into the body's most enigmatic workings and the moving story of a brilliant researcher's persistence against the odds."--